MANAJEMEN MODAL KERJA, PROFITABILITAS DAN NILAI PERUSAHAAN SEKTOR MANAUFAKTUR DI PT BURSA EFEK INDONESIA - TAUFIK . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The objective of this study is to analyze the influence of working capital management (i.e. quick ratio, inventory turnover, receivable turnover, net working capital turnover and current ratio) to profitability and firm value of manufacturing companies of the year of 2006 - 2010 at the Indonesian Stock Exchange. This research divided manufacturing firms into two types, first firms with increasing working capital and second firms with decreasing working capital. Purposive sampling is used in this research. Off 145 firms, only 18 firms with increasing working management and 18 firms with decreasing working management are carried out as samples in this research. Regression analysis was implemented to see the influence of working capital management to profitability and firm value. The result showed that quick ratio, receivable turnover had positive influence on profitability and net working capital turnover had negative influence on profitability at the firms with increasing working capital. Quick ratio had negative influence on firm value at the firm with increasing working capital. For firms with decreasing working capital, only quick ratio had positive influence on profitability and current ratio had negative influence on firm value. Due to some limitation of this research, it is suggested to include other related variables and other sectors of companies at the Indonesian Stock Exchange.